Assessing the Evaluability of Adaptation-Focused Interventions: Lesson s from the Adaptation Fund - MacPherson, Ronnie; Jersild, Amy; Bours, Dennis; Holo, Caroline (Transformational Change for People and the Planet: Evaluating Environm ent and Development, 2022)
Evaluability assessments (EAs) have differing definitions, focus on va rious aspects of evaluation, and have been implemented inconsistently in the last several decades. Climate change adaptation (CCA) programmi ng presents particular challenges for evaluation given shifting baseli nes, variable time horizons, adaptation as a moving target, and uncert ainty inherent to climate change and its extreme and varied effects. T he Adaptation Fund Technical Evaluation Reference Group (AF-TERG) deve loped a framework to assess the extent to which the Fund’s portfolio o f projects has in place structures, processes, and resources capable o f supporting credible and useful monitoring, evaluation, and learning (MEL). The framework was applied on the entire project portfolio to de termine the level of evaluability and make recommendations for improve ment. This chapter explores the assessment’s findings on designing pro grams and projects to help minimize the essential challenges in the fi eld. It discusses how the process of EA can help identify opportunitie s for strengthening both evaluability and a project’s MEL more broadly . A key conclusion was that the strength and quality of a project’s ov erall approach to MEL is a major determinant of a project’s evaluabili ty. Although the framework was used retroactively, EAs could also be u sed prospectively as quality assurance tools at the pre-implementation stage.